The relationship between university research and the surrounding communities in developing countries : a case study of the University of Venda for Science and Technology - Mashamba, Tshilidzi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.